Enamel surface roughness evaluation after bracket debonding: Comparison between light cure and self cure adhesive resin 3-Dimensional profilometric study - Deepak Chandrasekharan; Chandan Sourabh; Deenadayalan; Katepogu Praveen (Wolters Kluwer Medknow Publications, 2022)
Introduction: After fixed orthodontic treatment, following bracket removal, the debonding procedure should lead to restitutio ad integrum of the enamel or, at least, restore the enamel surface as closely as possible to its pretreatment condition. Adhesion of brackets in orthodontics is that they should be strong enough to prevent failure during all treatment but also low enough, so that enamel damage would be minimal during bracket removal after treatment. Material and Methods: A total of 60 premolars were collected and stored in distilled water. The extracted teeth were divided into two groups of 30 each, group A was to be bonded with self-cure adhesive while group B light cure adhesive was to be used. A standardised protocol was followed for adhering the brackets to the tooth surfaces. All the teeth were bonded with metal brackets (3M Unitek, Gemini Twin Brackets 0.022 slot). In group A, bonding adhesive (3M Unitek self cure adhesive primer) was applied. In group B, the bonding adhesive (3M Unitek light cure adhesive primer) was photopolymerized for 10 seconds after application. Results: Surface roughness of enamel as assessed by profilometry shows that light cure adhesive creates more roughness as compared to self cure adhesive. To conclude, self cure adhesive is clinically better than light cure adhesive. Discussion: In the present study enamel surface roughness were compared after debonding. Enamel surface roughness after bracket debonding depends on a host of factors, which include - brackets, adhesive used and method of remnant removal.